Observation of gauge boson joint-polarisation states in W±Z production from pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physics letters, 2023)
Measurements of joint-polarisation states of W and Z gauge bosons in W±Z production are presented. The data set used corresponds to an integrated luminosity of 139 fb−1 of proton-proton collisions at a centre-of-mass energy of 13 TeV recorded by the ATLAS detector at the CERN Large Hadron Collider. The W±Z candidate events are reconstructed using leptonic decay modes of the gauge bosons into electrons and muons. The simultaneous pair-production of longitudinally polarised vector bosons is measured for the first time with a significance of 7.1 standard deviations. The measured joint helicity fractions integrated over the fiducial region are f00=0.067±0.010, f0T=0.110±0.029, fT0=0.179±0.023 and fTT=0.644±0.032, in agreement with the next-to-leading-order Standard Model predictions. Individual helicity fractions of the W and Z bosons are also measured and found to be consistent with joint helicity fractions within the expected amounts of correlation. Both the joint and individual helicity fractions are also measured separately in W+Z and W−Z events. Inclusive and differential cross sections for several kinematic observables sensitive to polarisation are presented.
Online verfügbar: 7. Juni 2023, Artikelversion: 19. Juni 2023
Gesehen am 17.05.2024
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel sind die Zeichen + und - hochgestellt
*The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2910 weitere Personen]